INHERITANCE STUDIES OF GRAIN YIELD IN AFRICAN YAM BEAN (SPHENOSTYLIS STENOCARPA (HOCHST EX. A. RICH.) HARMS) - Agbowuro, Gbenga Oluwayomi; Salami, Ayodeji Ekundayo (Polish Journal of Natural Sciences, 2024)
African yam bean (AYB) is a tropical underutilized legume serving as food and feed. Despite its nutritional values, low grain yield limits its production. Overcoming low grain yield through the breeding programme requires adequate information on the inheritance pattern of the traits responsible for low grain yield. However, there is dearth information for AYB. Two divergent grain yield potential AYB accessions collected from the International Institute of Tropical Agriculture, Ibadan Nigeria were crossed to generate F1. The F1 was advanced to F2 progenies. Backcrosses to the two parents (BC1 and BC2) were generated. The six generations obtained were evaluated in three agroecological environments. Data collected on grain yield and grain yield-related traits were subjected to analysis of variance. Generation mean analysis and scaling tests were estimated. The results revealed that at least one of the scaling tests was significant in all the studied traits. The dominance gene effects were larger than additive gene effects in the studied traits. Complementary epistasis was observed in some studied traits while duplicative epistasis was observed in other studied traits. Environmental variances were less than genotypic variances in all studied traits. The traits studied exhibited high broad sense and low narrow sense heritability. The results showed that both additive and non-additive gene actions are important in inheriting these traits. Hence, reciprocal recurrent selection is the most suitable breeding procedure to improve AYB grain yield.